Analysis of Company Financial Performance Using EVA & MVA at PT. Adaro Energy Tbk. Period 2016-2020 - Vicky Fitria Rahayu Setyowati; Mursidi Mursidi; Erna Retna Rahadjeng (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to analyze and evaluate the company's financial performance using Economic Value Added (EVA) and Market Value Added (MVA) at PT. Adaro Energy Tbk. 2016-2020 period. This research uses quantitative research. Using secondary data in the form of financial reports and annual reports at PT. Adaro Energy Tbk for the 2016-2020 period published by the Indonesia Stock Exchange. Data collection techniques using the method of documentation. The results showed the results of the analysis of the financial performance of PT. Adaro Energy Tbk using EVA is said to be good because the EVA value is > 0. By using the EVA method through its translation in the form of NOPAT, Investor Capital, WACC, and Capital Charges, the final value of EVA is positive in the 2016-2020 period. The results of the analysis of the financial performance of PT. Adaro Energy Tbk using MVA is said to be good because the MVA value is > 0. Using the MVA method a positive value is obtained in the 2016-2020 period.